Alliance and CCAFS support to transform the use of data for decision making to accelerate growth in the livestock sector in Ethiopia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The Alliance, the Ethiopia government and CCAFS have produced a document that influenced the architectural roadmap development of livestock information system to support the federal ministry of agriculture. As a result, the roadmap and strategy will be used to align implementation of projects and design solutions with government priorities, align donors and funding to support government policies and plans, and prioritize investments, policies, and strategic planning. Implementation of the design would come in subsequent phases.